The Bossy Gallito - Lucia M Gonzalez (U.S.A Scholastic Inc., 1994)
A bilingual retelling of the popular Cuban folktale about a bossy little rooster. Includes a glossary and notes from the author and illustrator about characters and Cuban traditions.
Keywords: Read Aloud -- Read Aloud